PRANAYAMA SEBAGAI SAINS SPIRITUAL - Maharani, Ni Putu Rosa Agustina (JURNAL YOGA DAN KESEHATAN, 2019)
'Pranayama' consists of: Puraka which is entering the breath, Kumbhaka which is holding your breath, and Recaka is exhaling. But from the essence of pranayama is the ability to take and manage prana especially by using breath. In spiritual life, Pranayama's role depends on the individual. They feel that by asking for Protection, Peace and the Light of God they can change their nature and purify their lives as effectively as possible by doing Pranayama. The only breathing exercise that a spiritual candidate needs is to try to breathe pure. Control over the flow of prana in the vital body which calms the mind and limits the thought process, which is an important introduction to spiritual exercises. In the text of yoga sutra patanjalai pranayama is explained in the shadana padha sutra 49 which explains what the meaning of pranyama, sutra 50-51 describes the practice of pranayama, In Yoga Sutra, Patanjali describes pranayama as a process where they can break their subconscious breathing patterns and make long breath, subside, and smooth. The subconscious breathing pattern of some people is not easy and smooth; They tend to be tense, superficial, and erratic. Pranayama can also be practiced through java pranama, pranyama also has many techniques to practice pranyama, spiritual seekers get peace of mind. As long as some breathing techniques are slowed down and the strength of the exhaled air decreases. The well-known breathing techniques teach how to activate, stimulate energy that makes a person feel calm, relaxed, and comfortable. The purpose of pranayama is to reduce the speed of breathing / slow down breathing, Prana will be calm with a slow / slow breathing process. The mind will calm down, When breathing activity decreases, the activity of the mind will decrease, Between mind and prana are the senses.